LEAVING HOME TO COME HOME: REBUILDING JOURNALISTIC GATE-KEEPING ONE FACT AT A TIME - Todd, Paula Joy (AoIR Selected Papers of Internet Research, 2021)
Confusion about modern post-publication fact-checking is dissipating as the practise nears its 20th anniversary in the United States (where it began in earnest), and misinformation settles as a resistant and sometimes deadly drag on reality. But a nuanced analysis of fact-checking’s role in and on the journalistic field (Bourdieu, 1993, 1998; Benson & Neveu, 2010) is troubled by such independent characterizations of post hoc claim verification as: a revolt against journalism; a professional or social reform movement; a new genre; an entrepreneurial exercise; a status-seeking ploy; and/or a psychologically ineffective or damaging reinforcement of falsehoods. Given that accuracy is an ethical requirement of normative journalism and the defining characteristic of ‘news’( hence the political duplicity of the oxymoronic term, ‘fake news’), the birth of independent fact-checking troubles the practice of journalism and, by proxy, political knowledge, and can thus also be read as critique of the field writ large. While gatekeeping (Lewin, 1947) is assumed dead, and gate-watching (Bruns, 2003) on life support, modern fact-checkers are nevertheless culling and privileging information, while simultaneously adjudicating and assigning blame for public speech, which traditional ‘neutral’ journalism avoids. Using both both academic and journalistic qualitative and quantitative interview tools, and framed by field, gatekeeping/watching, and discourse theories (thus emulating the journalistic-academic hybrid model deployed in fact-checking), I examine the largely unexplored area of journalistic re-entrenchment and introduce the reverse-gate-keeping theory of ‘information corralling’ in the era of escalating misinformation.